Bottleio: smart LED display thermos / Amyra Natasha Shaiful Adly ... [et al.] - Shaiful Adly, Amyra Natasha; Safuan Zafwan, Fatin Farhana; Mohd Fauzi, Muhammad Faiz Hakimi; Roslan, Nur Hanis Haziqah (2020)
Bottleio, a company that is specialist in manufacturing Smart LED display thermos, based in Setia Alam, Selangor. Bottleio company offering customer an experience of owning an affordable luxury thermos to commute with their healthy lifestyle. We provide a practical convenient thermos with elegant looks suitable to all ages range. This product aiming to give a refreshing impact in health care product. Our product genuinely suitable for all because basically, we need a great quality container to contain the water which is the most important basic need of human resource. This thermos will assist their user as there is smart LED screen implanted to the body of the thermos that shows important information such as clock, day and date, water temperature in instance glance without having to look up on our gadget frequently and it will have a special effects which a blinking system o the display to notify the user that they need to drink their water.